FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN SECARA MAKRO DI LIMA BELAS PROVINSI TAHUN 2007 - Saputro, Agung Eddy Suryo; Utomo, Agung Priyo (Jurnal Organisasi dan Manajemen, 2010)
One factor which influences the success of poverty alleviation program is to determine where the poverty is concentrated. There are 15 provinces that have a value index of poverty depth (P1) higher than the value of P1 Indonesia. This study will describe the characteristics of poverty in 15 provinces; identify key factors affecting poverty at the macro level; and the relationship between each of the major factors in P1. Based on factor analysis obtained there are three main factors that characterize the 15 poor provinces, which are employment, education, and residence. Logistic regression analysis showed the relationship between employment factors and education with the negative P1. Both employment and educational factors have a significant effect on P1. Meanwhile, factor of residence was positively related to P1 but the effect is not significant.